2013
DOI: 10.2478/hukin-2013-0077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Analysis of the Acute Effects of a Heavy Resistance Exercise Warm-Up on Agility Performance in Court-Sport Athletes

Abstract: The purpose of this study was to determine the acute effects of heavy resistance exercise on agility performance in court-sport athletes. Five men (age: 20.6 ± 1.9 years; body mass: 79.36 ± 11.74 kg; body height: 1.93 ± 0.09 m) and five women (age 21.2 ± 2.7 years; body mass: 65.8 ± 10.18 kg; body height 1.77 ± 0.08 m) volunteered to participate in the present study. All subjects were NCAA Division II athletes who currently participated in tennis or basketball and all had previous resistance training experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 28 publications
(40 reference statements)
1
33
0
1
Order By: Relevance
“…For researchers, assessing COM velocity is often not as great a challenge in comparison to practitioners, hence the recent use of COM velocity in some recent research studies (78,88,89,102). However, the cost (financial and time) associated with measurement of COM velocity from three-dimensional analysis (e.g.…”
Section: Validity Of Current Cod Measures: Different Results Based Onmentioning
confidence: 99%
“…For researchers, assessing COM velocity is often not as great a challenge in comparison to practitioners, hence the recent use of COM velocity in some recent research studies (78,88,89,102). However, the cost (financial and time) associated with measurement of COM velocity from three-dimensional analysis (e.g.…”
Section: Validity Of Current Cod Measures: Different Results Based Onmentioning
confidence: 99%
“…In contrast, other studies concluded that performance after a PAP inducing activity was not related to training status (McBride et al, 2005). Furthermore, it has been proposed that the PAP may be related to the type of muscle fiber being activated (Wilson et al, 2013), with a higher proportion of fast fibers being related to greater PAP effect (Sole et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Agility can be defined as an ability to quickly and efficiently change the direction and/or speed of movement ( Sekulic et al, 2013 ). It is generally accepted that agility is an important quality in most sports where a quick and effective pre-planned or non-planned change of the direction is required ( Sattler and Sajber, 2015 ; Sole et al, 2013 ). To clearly distinguish between capacity when an athlete: (i) has advanced knowledge of the necessary change of the direction (i.e.…”
Section: Introductionmentioning
confidence: 99%